63 up - Apted, Michael 1941-2021 (ITV studios limited, 2019)
"Director Michael Apted revisits the same group of British-born adults after a 7 year wait. The subjects are interviewed as to the changes that have occurred in their lives during the last seven years." [imdb.com]
Original: Großbritannien 2019
Bildformat 1.78:1
Titelzusatz von DVD-Hülle: the ninth documentary in the landmark series
includes the celebrity documentary 7 up & me
Keywords: Geschichte 2012-2019; Briten; Siebenjahrperiode; Biografie; Großbritannien; Film; DVD-Video